Safeguarding agricultural land in spatial planning – Results of a nationwide plan content analysis - Hüppauff, Jakob (Raumforschung und Raumordnung | Spatial Research and Planning, 2026)
Land use changes in Germany mainly affect agricultural land. Demands on these areas are increasing and exceeding the amount of land available. Previous efforts to reduce the use of open spaces and move towards a circular economy have failed to meet political targets (e.g., the 30-hectare target). Unlike other land uses, arable land is less protected by law. Therefore, spatial planning plays a special role in securing (high-quality) agricultural land. However, the demands on agricultural land extend (far) beyond spatial planning and pose challenges for the planning and implementation of future land use options. Against this background, the article analyses the spatial planning specifications for safeguarding agricultural land and assesses them in terms of land-related spatial claims and aspects of food security. In particular, from a spatial balance perspective, it highlights the contribution that regional planning currently makes to avoiding irreversible losses of productive land to limit supra-regional land displacement effects with negative consequences for near-natural areas. The results confirm a fundamental need for discussion about the role of spatial planning in balancing land-related spatial demands.